Застосування сенсорних датчиків - Паненко, Р. В. (ХНУРЕ, 2025)
Sensors are key components of modern technologies, providing automation, security, environmental monitoring and efficient energy management. They are used in industry, medicine, transport and everyday life, improving the quality of life and optimizing work processes. Thanks to them, the development of smart cities, unmanned transport and environmental monitoring is possible. Sensors play an important role in ensuring safety, controlling gas levels, temperature and access to information. They contribute to the efficient use of resources.
Keywords: застосування сенсорних датчиків; сенсорний датчик